Severe gastrointestinal involvement in adult-onset Henoch–Schönlein purpura associated with clarithromycin-resistant Helicobacter pylori infection - Delgado García, Guillermo Rubén; Mandujano Cruz, Ilse; González Padilla, Kiber; Hernández Velázquez, Badir; Martínez Cabriales, Sylvia Aideé; Ocampo Candiani, Jorge; Villarreal Alarcón, Miguel Ángel; Galarza Delgado, Dionicio Ángel (2016)
Background: Henoch–Scho¨nlein purpura (HSP) is an uncommon vasculitis in adults. Gastrointestinal involvement is part of the classical tetrad and can present as bleeding. Helicobacter pylori infection in the setting of HSP has been reported a few times in the literature and may be involved in the pathogenesis of this disease as a triggering agent.